Improving Electoral Integrity with Information and Communications Technology. Issue 1 (26th October 2015) - Callen, Michael; Gibson, Clark C.; Jung, Danielle F.; Long, James D.
Abstract: Irregularities plague elections in developing democracies. The international community spends hundreds of millions of dollars on election observation, with little robust evidence that it consistently improves electoral integrity. We conducted a randomized control trial to measure the effect of an intervention to detect and deter electoral irregularities employing a nation-wide sample of polling stations in Uganda using scalable information and communications technology (ICT). In treatment stations, researchers delivered letters to polling officials stating that tallies would be photographed using smartphones and compared against official results. Compared to stations with no letters, the letters increased the frequency of posted tallies by polling center managers in compliance with the law; decreased the number of sequential digits found on tallies – a fraud indicator; and decreased the vote share for the incumbent president in some specifications. Our results demonstrate that a cost-effective citizen and ICT intervention can improve electoral integrity in emerging democracies.